What is time to a pig? - Straley, John, 1953- (The Cold Storage novels, 2020)
"It's been seven years since Gloomy Knob landed in the Ted Stevens High-Security Federal Penitentiary and five years since the end of the war, the one North Korea started when they sent a missile to Cold Storage, Alaska. Serving a life sentence for the murder of his sister, Gloomy spends his time trying to forget about the past. Then one day, an old family friend grabs Gloomy from his off-site work station and smuggles him away in a hollow tree trunk. Instead of celebrating his newfound freedom, Gloomy finds himself slowing coming unmoored. Prison is where he feels he belongs for the unspeakable wrongs he has committed, but his kidnappers have other plans. They want information from Gloomy, and they want it soon, or his wife, his friends, and the entire town of Cold Storage may all get obliterated. As Gloomy struggles to escape, the memories he fought hard to repress begin to creep out from the strange corners of his mind, first in rivulets, then in waves. In a drug-induced haze, Gloomy decides to wade in, and what he discovers may just bring him the closure he desires-if it doesn't kill him first"--